Analisis Peran Konten Instagram Universitas dan Loyalitas Mahasiswa terhadap Peningkatan Reputasi Universitas Kota Batam - Muhammad Ardiansyah (Universitas Hamzanwadi, 2021)
A university is required to continuously improve its reputation and with the help of social media (SocMed), the university can grow its reputation through providing content and increasing loyalty through SocMed. The purpose of this study is to analyse the number of SocMed users among students at higher-education institutions, the importance of providing SocMed content, Instagram SocMed content can be considered as good in providing information, Student’s loyalty toward university’s reputation, as a consideration for a university in considering the type of content and interaction that will be carried out to students via SocMed, and to determine the importance of student’s loyalty toward university. This study uses quantitative methods with Content on the university's Instagram SocMed and student’s loyalty as the independent variables, and the University's reputation as the dependent variable. The questionnaire was distributed online using google form. As for data processing, SPSS-App, and data analyst, using regression with several tests consists of data validity-test, data reliability-test, normality-test, and correlation-test. The samples in this study were 395 students from universities in the city of Batam. This study proves that the University's SocMed Content has an influence on the university's reputation, and Student’s Loyalty also affects the university's reputation in the social-environment.